Victor Bérard et la Macédoine - Ivan Savev (Cahiers Balkaniques)
In 1878, the Congress of Berlin had left Macedonia in the hands of the Ottomans. Greece, Serbia and Bulgaria had reached its limits. Anticipating the Ottoman retreat, they polish language and historical arguments that will justify their territorial claims. Victor Bérard, a respected Hellenist and a good expert of the southern Balkans, is doing researches in Macedonia in 1896 and 1903. These will be later published in Paris.This study shows how, in the context of the nationalist propaganda build-up made by the candidates for the possession of Macedonia, Victor Bérard comes progressively to assert the existence of a native population: the Macedonians. He supports their program for the forming of a federation or confederation which slogan would be “Macedonia to Macedonians”. This makes his works very topical.